Rapid detection reagent for gastric cancer marker in saliva as well as preparation method and application of rapid detection reagent
By using SERS technology of composite nanomaterials and signaling molecule 3-MPBA, rapid, sensitive and selective detection of gastric cancer markers D-Pro and D-Ala in saliva is achieved, solving the problem of difficulty and susceptibility to detection in the prior art, reducing costs and simplifying sample processing.
Patent Information
- Application Number
- CN202411573777.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to achieve high sensitivity, high selectivity and rapid detection of gastric cancer markers D-Pro and D-Ala in saliva, and traditional methods are susceptible to interference, costly, and uncomfortable.
The composite shell structure of the composite nanomaterial cobalt-polyphenol nanospheres outsourced silver nanoparticles is adopted, and combined with the signal molecule 3-MPBA, the rapid detection of gastric cancer markers in saliva is achieved through surface-enhanced Raman scattering (SERS) technology.
High sensitivity, selectivity and rapid detection of gastric cancer markers D-Pro and D-Ala in saliva is achieved, reducing detection costs, simplifying sample processing, and has anti-interference ability.
Smart Images

Figure CN119643528A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of gastric cancer marker detection in saliva, and specifically to a rapid detection reagent for gastric cancer marker in saliva, a preparation method thereof, and an application thereof. Background Art
[0002] Gastric cancer is one of the most common cancers with the highest morbidity and mortality rates worldwide. Early diagnosis and timely treatment of gastric cancer can effectively reduce the high mortality rate of gastric cancer. However, traditional diagnosis mainly relies on PET-CT, endoscopy and biopsy, which are costly, time-consuming, invasive and uncomfortable. Therefore, there is an urgent need to explore non-invasive and low-cost screening methods to detect biomarkers related to gastric cancer. It has been reported that during the development and progression of gastric cancer, tumor cells release a variety of metabolites into the blood and saliva, including D-alanine ( D -Ala) and D-proline ( D -Pro). Therefore, D -Pro and D The identification of -Ala can be used as a biomarker for gastric cancer diagnosis. D -Pro and D The concentration of -Ala is of great significance for the diagnosis and treatment of gastric cancer.
[0003] Molecular chirality is a ubiquitous phenomenon in nature and is closely related to the origin of life. Enantiomers of chiral molecules exhibit different pharmacological, biological, and pathological activities despite having the same physical and chemical properties. Representatively, amino acids usually exhibit left-handed (L) amino acids (L-AAs) rather than right-handed (D) amino acids (D-AAs). However, D-AAs have attracted increasing attention due to their potential association with diseases and the different roles they play in organisms, including bacteria, plants, and other organisms. For example, D-serine regulates n-methyl d-aspartate receptors (NMDARs) and affects synaptic plasticity, neural development, learning, memory, and neural metabolism. Therefore, sensitive detection of D-AAs is of great significance for clinical diagnosis.
[0004] Compared with L-AAs, D-AAs are right-handed and have positive spin. At present, the traditional analytical methods are mainly circular dichroism and liquid chromatography, but expensive chiral chromatographic columns or complex chiral probes are required to assist enantiomer identification. In addition, due to low sensitivity and susceptibility to interference from other substances, other methods such as fluorescence and spectrophotometry cannot effectively monitor similar amino acids with different parts. Therefore, it is necessary to design a simple and sensitive chiral identification and quantitative detection method. New methods such as polarized light, colorimetry, and Raman spectroscopy with new heterogeneous materials as separation and detection media have good application prospects in the separation and analysis of chiral substances. Recently, the use of surface enhanced Raman scattering (SERS) spectroscopy to identify the enantiomers of chiral molecules has become a new trend. As a forward-looking technology with high sensitivity, non-destructive detection capability and excellent molecular fingerprint specificity, SERS has been widely used in chemical identification in multidisciplinary fields. Generally, SERS materials have poor stability, are easily affected by environmental factors, and are often interfered by L-AAs. Therefore, it is urgent to design a material that is anti-interference and specifically detects D-AAs.
[0005] In view of this, the present application proposes a rapid detection reagent for gastric cancer markers in saliva, its preparation method and application, which is of great significance and broad application prospects for realizing an instant gastric cancer marker monitoring system in saliva with high sensitivity, high selectivity, short response time and simple sample processing. Summary of the invention
[0006] The purpose of the present invention is to provide a rapid detection reagent for gastric cancer markers in saliva, its preparation method and application, and to address the deficiencies in the prior art, so as to achieve rapid detection of gastric cancer markers, which is fast, accurate and easy to promote and use.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a rapid detection reagent for gastric cancer markers in saliva, the detection reagent comprising a composite nanomaterial and a signal molecule 3-MPBA, wherein the composite nanomaterial is a composite material shell structure of cobalt-polyphenol nanospheres coated with silver nanoparticles.
[0009] In a second aspect, the present invention provides a method for preparing a rapid detection reagent for gastric cancer markers in saliva, comprising the following steps:
[0010] S11, dissolve F127 in a mixed solution of ethanol and ammonia, stir evenly, add tannic acid solution and formaldehyde solution to react, and add Co(NO 3 ) 2 The solution was subjected to hydrothermal treatment and centrifugal drying to obtain the Co-TA nanocomposite material;
[0011] S12, adding the silver ammonia solution to the Co-TA nanocomposite material to react, thereby obtaining a Co-TA@Ag solution;
[0012] S13. After adding 3-MPBA solution and acetate buffer to the Co-TA@Ag solution, incubate at room temperature to finally obtain the detection reagent.
[0013] Preferably, in step S11, the mass of F127 is 0.1-0.3 g; the mixed solution of ethanol and ammonia is configured in the following proportions: the volume of ethanol is 8-10 ml, the volume of ultrapure water is 30-50 ml; the mass fraction of the ammonia solution is 25 wt%, and the volume is 0.1-0.5 mL; the stirring time is 30-60 min.
[0014] Preferably, in step S11, the volume of the tannic acid solution is 4-5 mL, the mass fraction of the formaldehyde solution is 37 wt %, the volume of the formaldehyde solution is 4-5 mL, and the reaction time of the tannic acid solution and the formaldehyde solution is 12-24 h.
[0015] Preferably, in step S11, Co(NO 3 ) 2 The concentration of the solution is 80-100 mg / mL, Co(NO 3 ) 2 The volume of the solution is 1 to 2 mL, the heating temperature of the hydrothermal treatment is 80 to 100° C., the heating time is 10 to 12 h, the centrifugal speed is 7000 rpm, and the centrifugal time is 10 to 15 min.
[0016] Preferably, in step S12, the volume of the Co-TA nanocomposite material after dilution is 20 to 30 mL, the rate of adding the silver ammonia solution is 100 to 300 μL / min, the concentration of the silver ammonia solution is 10 to 30 mg / mL, and the volume of the silver ammonia solution is 10 to 20 mL; the reaction time of the silver ammonia solution and the Co-TA nanocomposite material is 20 to 50 min.
[0017] Preferably, in step S13, the volume of Co-TA@Ag solution is 50-100 μL, the volume of 3-MPBA solution is 10-100 μL, the concentration of 3-MPBA solution is 50-100 μM, the volume of acetate buffer is 10-50 μL, the concentration of acetate buffer is 5-10 mM, the pH of acetate buffer is 3.6, and the incubation time at room temperature is 3-6 h.
[0018] In a third aspect, the present invention provides a method for preparing a rapid detection reagent for gastric cancer markers in saliva, and the use of the prepared detection reagent in detecting gastric cancer markers contained in saliva, comprising the following steps:
[0019] S21, diluting the saliva sample to be tested with PBS buffer, centrifuging and filtering with a filter membrane to obtain a sample to be tested;
[0020] S22, reacting the sample to be tested with the detection reagent to determine the sample value, recording the intensity response of the Raman spectrometer, and calculating different D-Pro / Ala concentrations according to the standard curve, and repeating each sample to be tested multiple times.
[0021] Preferably, in step S21, the volume of the sample to be tested is 1-2 mL, the concentration of PBS buffer is 10 mM, the pH is 7.4, and the volume is 5-10 mL; the centrifugal speed is 3000-5000 rpm, the centrifugal time is 5-10 min, and the pore size of the filter membrane is 0.45 μm.
[0022] Preferably, in step S22, the conditions for the Raman spectrometer measurement are: the laser wavelength is 585-785 nm, the laser power is 30-50 mW, and the signal integration time is 1-5 s.
[0023] Compared with the prior art, the beneficial results of the present invention are:
[0024] (1) The chiral separation behavior of heterogeneous structural materials composed of multiple metals (Co, Ag) and organic ligands (chiral polyphenols) is stronger. The prepared cobalt-polyphenol heterogeneous materials usually contain bimetallic structures, forming bimetallic active centers with strong electron transfer behavior. Polyphenol compounds promote redox reactions and electron transfer by providing active sites and regulating reaction pathways. In addition, polyphenols can also form catalytic structures with metal ions, similar to the active centers of natural enzymes. Therefore, the superior electron transfer behavior gives the metal polyphenol complex enhanced SERS activity and nanozyme catalytic behavior. Compared with natural enzymes, the detection reagent Co-TA@Ag nanocomposite material in the present invention has the advantages of high stability, low cost, easy synthesis and modification, etc., and has broad application prospects in the detection of disease-related biomarkers such as lung cancer and heart disease.
[0025] (2) Due to its high reactivity, the α-H bond of D-AAs can be easily oxidized and change its structural properties. Therefore, the bimetallic nanozyme conjugated SERS method will provide a more readable and quantifiable output signal for the detection of D-AAs in gastric cancer. This can achieve rapid detection of gastric cancer markers in saliva, which has good application prospects in instant medical testing and health care. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:
[0027] Figure 1It is a schematic diagram of the synthesis of nanoparticles in performance test 1 of the embodiment of the present application;
[0028] Figure 2 is a scanning electron microscope image of the nanoparticles (Co-TA) in performance test 1 of the embodiment of the present application;
[0029] Figure 3 is a scanning electron microscope image of the nanoparticles (Co-TA@Ag) in performance test 1 of the embodiment of the present application;
[0030] Figure 4 is a transmission electron microscope image of the nanoparticles (Co-TA@Ag) in performance test 1 of the embodiment of the present application;
[0031] Figure 5 is the EDS image of the nanoparticles in performance test 1 of the embodiment of the present application;
[0032] Figure 6 is a HRTEM image of the nanoparticles (Co-TA@Ag) in performance test 1 of the embodiment of the present application;
[0033] Figure 7 It is the SAED selected area electron diffraction pattern of the nanoparticle Co-TA@Ag in the performance test 1 of the embodiment of the present application;
[0034] Figure 8 In the performance test 2 of the embodiment of the present application, (a) is an ultraviolet visible absorption spectrum (UV-vis) diagram (the horizontal axis is the ultraviolet spectrum wave number, and the vertical axis is the ultraviolet spectrum absorbance);
[0035] (b) Fourier transform infrared spectra (FT-IR) of Co-TANPs and Co-TA@AgNPs.
[0036] (c) X-ray diffraction (XRD) spectra of Co-TANPs and Co-TA@AgNPs.
[0037] (d) Range X-ray photoelectron spectroscopy (XPS) spectrum of Co-TA@AgNPs.
[0038] (e) Ag3d spectrum; (f) Co2p spectrum; (g) C1s spectrum; (h) O1s spectrum; (i) N1s spectrum;
[0039] Fig. 9 The Co-TA@Ag nanozyme biosensor studied in performance test 3 of the present application example was ABTS-H 2 O 2 Color development system mechanism;
[0040] Fig.10It is the UV-visible absorption spectrum and colorimetric response of the Co-TA@Ag nanozyme biosensor reaction system in performance test 3 of the embodiment of the present application;
[0041] Fig.11 It is the steady-state kinetic analysis of ABTS oxidation catalyzed by Co-TA@Ag nanozyme biosensor in performance test 4 of the embodiment of the present application;
[0042] Fig.12 The Co-TA@Ag nanozyme biosensor catalyzed H 2 O 2 Steady-state kinetic analysis of oxidation;
[0043] Fig.13 The EPR measurement was performed using a DMPO / TEMP probe in performance test 5 of the present embodiment;
[0044] Fig.14 This application implements performance test 6 differently D -SERS spectra at Pro / Ala concentrations (5-1000 μM);
[0045] Fig.15 The I654 / I1077 to 10mM D -Pro / Ala and others 100mM D -SERS response diagram of Pro / Ala;
[0046] Fig.16 There are 10 different performance tests in the embodiment of this application 7 D -c-normal probability plot of Pro / Ala;
[0047] Fig.17 The I654 / I1077 to 5mM D -10 SERS response graphs of Pro / Ala;
[0048] Fig.18 This is a time stability test diagram in performance test 9 of the embodiment of the present application. DETAILED DESCRIPTION
[0049] The present application will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should also be noted that, for ease of description, only the parts related to the relevant invention are shown in the accompanying drawings.
[0050] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0051] Embodiment 1
[0052] The first embodiment of the present application discloses a rapid detection reagent for gastric cancer markers in saliva. The rapid detection reagent for gastric cancer markers in saliva includes a composite nanomaterial and a signal molecule 3-MPBA. The composite nanomaterial is a composite shell structure of cobalt-polyphenol nanospheres coated with silver nanoparticles (Co-TA@Ag). The nanocomposite material of cobalt-polyphenol coated with silver (3-MPBA:Co-TA@Ag NPs) is a L -TA acts as a polymer ligand and coordinates with Co ions to form chiral nanoparticles. L The unique redox properties of catechol / galloyl in -TA triggered the interfacial redox reaction and successfully loaded silver nanoparticles to prepare Ag-Co bimetallic dual-active center selective surface enhanced Raman scattering (SERS) nanocomposites with 3-MPBA as the signal molecule.
[0053] Embodiment 2:
[0054] Example 2 of the present application discloses a method for preparing a rapid detection reagent for gastric cancer markers in saliva. The method for preparing a rapid detection reagent for gastric cancer markers in saliva is prepared using the rapid detection reagent for gastric cancer markers in saliva, and comprises the following steps:
[0055] S11. Preparation of Co-TA nanocomposites: F127 (0.1 g) was dissolved in a mixed solution of ethanol / water (8 / 37 mL) and ammonia (25 wt%, 0.35 mL) and stirred for 1 hour. Then, tannic acid solution (5 mL, 0.02 g / mL) and formaldehyde solution (37 wt%, 0.5 mL) were added respectively. After reacting for 24 hours, Co(NO 3 ) 2 The solution (2 mL, 250 mg / mL) was hydrothermally treated at 100 °C for 12 h and centrifugally dried to obtain the Co-TA nanocomposite material.
[0056] In other embodiments, in step S11, the content of each component can also be any value within the following ranges: the mass of F127 (polyether ketone) is 0.1-0.3g; the mixed solution is prepared in the following proportions: the volume of ethanol is 8-10ml, the volume of ultrapure water is 30-50ml, the mass fraction of ammonia solution is 25wt%, the volume is 0.1-0.5mL, and the stirring time is 30-60min; the volume of tannic acid (TA) is 4-5mL, the mass fraction of formaldehyde solution is 37wt%, the volume of formaldehyde solution is 4-5mL, and the reaction time is 12-24h; the concentration of copper nitrate solution is 80-100mg / mL, the volume of copper nitrate solution is 1-2mL, the solution heating temperature is 80-100℃, and the heating time is 10-12h; the centrifugal speed is 7000rpm, and the centrifugal time is 10-15min.
[0057] S12, preparation of Co-TA@Ag nanocomposite materials, adding silver ammonia solution to the prepared Co-TA nanocomposite materials for reaction, and obtaining Co-TA@Ag NPs, a rapid detection reagent for gastric cancer markers in saliva.
[0058] In this embodiment, in step S12, the content of each component can be any value within the following range: the volume of the cobalt polyphenol nanosol after dilution is 20-30 mL, the addition rate of the silver ammonia solution is 100-300 μL / min, the concentration of the silver ammonia solution is 10-30 mg / mL, the volume of the silver ammonia solution is 10-20 mL, and the solution reaction time is 20-50 min.
[0059] Embodiment three:
[0060] The third embodiment of the present application discloses a kit, which comprises the above-mentioned rapid detection reagent for gastric cancer markers in saliva and PBS buffer, wherein the PBS buffer is used to dilute the saliva sample to be tested.
[0061] Embodiment 4:
[0062] Embodiment 4 of the present application discloses an application of a detection reagent in detecting gastric cancer markers contained in saliva, such as a detection method of a kit, the detection method of the kit comprising the following steps:
[0063] S21. Dilute the saliva sample to be tested with PBS buffer, centrifuge and filter with a filter membrane.
[0064] In other embodiments, in step S21, the content of each component may also be any value within the following ranges: the volume of the saliva sample to be tested is 1-2 mL, the concentration of the PBS buffer is 10 mM, the pH is 7.4, the volume is 5-10 mL, the centrifugal speed is 3000-5000 rpm, the centrifugal time is 5-10 min, and the pore size of the filter membrane is 0.45 μm;
[0065] S22, reacting the sample to be tested with a rapid detection reagent for gastric cancer markers in saliva to determine the sample value, recording the SERS intensity response, and calculating the different values of the measured value according to the standard curve. D -Pro / Ala concentration, each sample was repeated 3 times.
[0066] In other embodiments, in step S22, the content of each component may also be any value within the following range, and the conditions for Raman spectrometer measurement are: laser wavelength of 585-785 nm, laser power of 30-50 mW, and signal integration time of 1-5 s.
[0067] Performance Testing:
[0068] Performance Test 1:
[0069] Microscopy, spectroscopy and other techniques were used to observe the morphological and structural changes of the composite nanomaterial (Co-TA@Ag) in the detection reagent to verify its spectral behavior and clear core-shell structure, and the structure of the prepared nanoparticles was characterized by scanning electron microscopy and transmission electron microscopy.
[0070] Reference Figure 1 , in the prepared Co-TA@Ag nanomaterials, L -TA acts as a polymer ligand and coordinates with Co ions to form chiral nanoparticles. L The unique redox properties of catechol / galloyl in TA triggered the interfacial redox reaction and successfully loaded silver nanoparticles to prepare Ag-Co bimetallic dual-active center selective surface enhanced Raman scattering (SERS) nanomaterials.
[0071] Reference Figure 2 ,SEM images show that under this concentration of silver ammonia solution, the surface of the Co-TA spheres is basically surrounded by silver nanoparticles, and they are all spherical and uniform in size.
[0072] Reference Figure 3 ,SEM images show that the outside of the nanocomposite is surrounded by high-density Ag nanoparticles, and the AgNPs are gathered around Co-TA to form a stable SERS hotspot.
[0073] Reference Figure 4 , TEM images show that the nanocomposite is composed of Co-TA spheres inside and surrounded by high-density Ag nanoparticles outside.
[0074] Reference Figure 5,From the EDS spectrum and element counting diagram of Co-TA@Ag, it can be seen that Co-TA@Ag NPs are mainly composed of five elements: Co (2.39%), Ag (11.96%), O (17.59%), N (27.54%), and C (40.52%).
[0075] Reference Figure 6 , HRTEM of the nanoparticles measured the 220 diffraction pattern of Ag with a plane spacing of 0.235nm and the 111 diffraction pattern of the cobalt polyphenol material (lattice spacing of 0.212nm) to verify the formation of the nanocomposite material.
[0076] Reference Figure 7 The SAED selected area electron diffraction results show that the Co-TA@Ag nanoparticles have a mesoporous structure of 3.8 nm and a specific surface area of 14.7335 cm 2 / g, with excellent adsorption performance.
[0077] The above results indicate that Ag nanoparticles were successfully loaded on the surface of Co-TA spheres.
[0078] Performance Test 2:
[0079] Verify the atomic composition and surface binding properties of the composite nanoparticles, and perform FT-IR, XRD, and XPS tests on the materials.
[0080] Reference Figure 8 , UV-visible spectra of Co-TA and Co-TA@Ag ( Figure 8 a), as can be seen from the FT-IR detection diagram, the Ag spectrum (8b) shows two spin states of Ag 3d3 / 2 (374.32eV) and Ag 3d5 / 2 (368.32eV), indicating the presence of zero-valent Ag. Similarly, the Co 2p spectrum (Figure c) shows two spin states of Co 2p3 / 2 and Co 2p1 / 2, at 783.8eV and 796.65eV, respectively, indicating that Co is in a divalent state. These findings confirm that the metallic valence behavior of Co is mainly in a divalent state, while Ag mainly exists in a zero-valent state in the composite nanomaterial. Therefore, there will be a more stable valence transfer behavior between zero-valent Ag and divalent Co, which will effectively promote the redox behavior of Co nanozymes. With the formation of the Co-TA@Ag NPs complex, the spectral behavior changed significantly. UV-visible spectrum ( Figure 8g) shows a surface plasmon resonance (SPR) peak at 330 nm, corresponding to the silver nanoparticles, indicating that the catechol groups in the cobalt polyphenols successfully reduced the silver ions. The SPR peak of the cobalt polyphenols overlapped with the Ag NPs, resulting in significant changes in the dielectric constant and resonance frequency and enhanced valence state transfer capabilities. In addition, the characteristic vibration peaks of tannic acid (C = benzene ring at 1450 cm -1 The C-type stretching vibration of the carboxyl group is at 1725 cm -1 The C=O stretching vibration at 3300cm -1 Oh-type stretching vibration at ), which is consistent with the XPS results ( Figure 8 h). XRD spectrum of Co-TA NPs ( Figure 8 i) It shows obvious amorphous diffraction peaks within 25 degrees. In addition, the surface electrical properties of Co-TA NPs are negative charge ζ = -28.6mV, which becomes ζ = 4.8mV after immobilizing Ag NPs. Therefore, the multivalent metal and crystal surface of Co-TA@Ag NPs will promote the covalent reaction of boric acid with D-Pro / Ala and enhance the valence transfer ability in the system. This composite material is used as a Raman basis to realize the real sample D -Pro / Ala detection.
[0081] Performance Test 3:
[0082] To further characterize the catalytic activity of the nanocomposite, a typical color reaction was performed to study the activity of Co-TA@Ag nanomaterials. 2,2-Naphthalenenitride-(3-ethylbenzothiazole-6-sulfonic acid) acid ammonium salt (ABTS) has higher sensitivity and accuracy, is easily oxidized and discolored by free radicals, and has a clear absorption peak in the visible light region.
[0083] Reference Fig. 9 ABTS color development is the reaction between ABTS and Co-TA@Ag and H 2 O 2 Redox mixture mediated. 2 O 2 In the presence of 3-MPBA:Co-TA@Ag NPs nanozymes promote the conversion of colorless ABTS substrate into green oxidation product (ABTS), with a characteristic absorption peak at 415 nm. 2 O 2 UV-visible spectroscopic scanning was performed on the / ABTS system, proving that Co-TA@Ag has the ability to convert ABTS into ABTS· + of nanozyme activity.
[0084] 100 μL Co-TA@Ag was mixed with 200 μL acetate buffer (pH 3.6, 10 mM), 50 μL ABTS (10 mM) and 50 μL H 2 O 2 (0.03%) and mixed, and incubated at 25°C for 5 minutes. The catalytic performance of the catalyst was evaluated by UV-vis method.
[0085] Reference Fig.10 , when ABTS / H 2 O 2 When / Co-TA@Ag was present, the absorbance at 415 nm was significantly higher than that of ABTS / Co-TA@Ag and H 2 O 2 / Co-TA@Ag, indicating that the presence of Co-TA@Ag can promote the oxidation of ABTS.
[0086] Performance Test 4:
[0087] Nanozyme kinetic analysis of the test reagents in the present invention.
[0088] Kinetic analysis was performed at room temperature with the addition of ABTS (0.05 mM-1.0 mM) or H 2 O 2 (0.05mM-2.0mM), and the catalytic kinetic parameters were calculated by fitting the Michaelis-Menten equation V=(Vmax×[S]) / (Km+[S]), where V is the reaction rate, Vmax is the maximum reaction rate, [S] is the substrate concentration, and Km is the Michelis constant.
[0089] In a system containing ABTS, the material can promote H 2 O 2 The Michaelis-Menten equation was used to analyze the steady-state kinetics of 3-MPBA:Co-TA@Ag nanozyme, determine the maximum reaction rate (Vmax) and Michaelis-Menten constant (Km), and evaluate the affinity between the enzyme and the substrate.
[0090] V = (Vmax × [S]) / (Km + [S]) to calculate the catalytic kinetic parameters, where V is the reaction rate, Vmax is the maximum reaction rate, [S] is the substrate concentration, and Km is the Michelis constant.
[0091] like Fig.11 and Fig.12 As shown in Figure 2, the Vmax of Co-TA@Ag NPs nanozyme in ABTS substrate is 1.28×10 -8 Ms -1, while the Km value of 3-MPBA:Co-TA@Ag NPs nanozyme for ABTS was 1.37 mM, which was higher than that of HRP. These results indicate that 3-MPBA:Co-TA@Ag NPs nanozyme has a typical Michaelis-Menten behavior. 2 O 2 The kcat / Km value of the color development system was 1.8, which was 1.5 times that of HRP. Therefore, the prepared Co-TA@Ag mimetic enzyme exhibited excellent catalytic activity in various environments, with enhanced stability and effective activity.
[0092] Performance Test 5:
[0093] Electron spin resonance (EPR) experiments further confirmed that 5,5-dimethyl-1-pyridine n-oxide (DMPO) and 2,2,6,6-tetramethyl-4-piperidinone hydrochloride (TEMP) as spin trapping agents could generate superoxide anions, monoclinic oxygen ions, and hydroxyl radicals. 3-MPBA:Co-TA@Ag methanol solution (200 μL) was mixed with H 2 O 2 1 mL of 0.03% ethanol and 2 mL of 10 mM acetate buffer (pH 3.6) were mixed, and then 1 mL of DMPO / TEMP (500 mM) was added. The resulting solution was extracted with a quartz capillary and placed in a glass tube for EPR measurement.
[0094] like Fig.13 DMPO captures the short-lived and highly reactive HO · (hydroxyl radical) and O2·-(superoxide radical), forming DMPO-HO with characteristic spectral intensities of 1:2:2:1 and 1:1:1:1 respectively. · and DMPO-O2·-spin adducts. This indicates that Co-TA@Ag has the ability to catalyze the generation of HO · and O2 · In addition, TEMP is 1O 2 (1O 2 , singlet oxygen) to generate TEMP- 1 O 2 Taken together, these results indicate that the H 2 O 2 HO· and O 2 - and 1O 2 .
[0095] Performance Test 6:
[0096] In order to verify the composite nanomaterial 3-MPBA: Co-TA@Ag in the detection reagent of the present invention D -The response behavior of Pro / Ala was used for quantitative analysis and sensitivity detection.
[0097] 3-MPBA (10 μL, 100 μL) and 50 μL acetate buffer (10 mM, pH 3.6) were added to 100 μL Co-TA@Ag solution and incubated at room temperature for 6 h. D -Pro / Ala solution (5 μL), react at 25°C for 10 minutes. D -SERS signal changes of Pro / Ala.
[0098] Under optimal experimental conditions, D -Pro / Ala 50μL, 3-MPBA 100μL, Co-TA@Ag 150μL, reaction time 20 minutes, reaction temperature 25℃, pH 6, and the Co-TA@Ag substrate pair was obtained. D -SERS response of Pro / Ala concentration.
[0099] In other embodiments, the content of each component can also be any value within the following range: the volume of Co-TA@Ag solution is 50-100 μL, the volume of 3-MPBA solution is 10-100 μL, the concentration of 3-MPBA solution is 50-100 μM, the volume of acetate buffer is 10-50 μL, the concentration of acetate buffer is 5-10 mM, the pH of acetate buffer is 3.6, and the incubation time at room temperature is 3-6 h.
[0100] Reference Fig.14 and Fig.15 ,along with D -As the concentration of Pro / Ala decreases, the Raman signal of I654 / I1077 gradually increases. The results show that in the range of 5μM to 1000μM, D The R2 between the concentration of -Pro / Ala and the determination result is 0.943 and 0.990 respectively. Therefore, the detection reagent of the present invention can be used for quantitative analysis, and the method is relatively sensitive.
[0101] Performance Test 7:
[0102] The feasibility and anti-interference ability of the method of the present invention were evaluated.
[0103] In fact, saliva and serum samples are complex samples with many interferences (e.g., amino acids, metal ions, or reducing substances). Fig.16As shown, according to the above method, glutathione (GSH), glycine (Gly), cysteine (Cys), valine (Val), serine (Ser), threonine (Thr), K + 、Na + , Ca 2+ , CO 3 2- , Cu 2+ , Fe 2+ Mg 2+ 、Zn 2+ , H 2 PO 4- , HPO 4 2- , HCO 3- , Cl - ,I - 、SO 4 2- ). The I654 / 1077 value of interference is significantly lower than D -Pro / D The value of -Ala indicates that these interferences can be ignored.
[0104] Performance Test 8:
[0105] The reproducibility and stability of the test reagent 3-MPBA:Co-TA@Ag biosensor in the method of the present invention were evaluated to ensure that the nanomaterial can be used in practical applications.
[0106] like Fig.17 As shown, reproducibility was achieved by 5 mM D -Pro / Ala were evaluated by 10 parallel tests, and the relative standard deviation (RSD) of the sensor was close to 2.69%. Therefore, the nanomaterial can be used for practical applications.
[0107] Performance Test 9:
[0108] Verify that the material of the present invention has the same concentration after long-term storage D -SERS intensity changes of Pro / D-Ala, the materials were stored at 4 °C and measured regularly to obtain the Raman spectrum of the Raman substrate to PG.
[0109] like Fig.18 After 10 weeks of storage, for the same concentration D -Pro / D -Ala, the SERS signal response value of this method remains above 90%. D -Pro / D The detection of -Ala is specific, accurate and reliable and can be applied to actual sample detection.
[0110] Performance Test 10:
[0111] By measuring the D -Pro and D -Ala was used to verify the performance of 3MBA:Co-TA@Ag biosensor to evaluate its applicability in complex matrices.
[0112] The prepared 3-MPBA:Co-TA@Ag biosensor was used in gastric cancer patients D -Pro / Ala detection. Saliva samples were collected at the Affiliated Hospital of Xiamen Medical College after consent was obtained from volunteers without gastric cancer. Regarding saliva samples, all volunteers agreed to participate in this study, and 1 ml of saliva samples were collected from each volunteer. Saliva samples (1 mL) were diluted with PBS buffer (10 mM, pH = 7.4, 9 mL), centrifuged at 7000 rpm for 10 min, and filtered through a 0.45 μm filter membrane. The actual determination was performed as described above without any modification. Different D -SERS signal intensity of Pro / Ala and calculated its recovery to evaluate the degree of deviation.
[0113] Here, the detection reagent (3-MPBA:Co-TA@Ag) of the present invention is used to detect the presence of D -Pro and D -Ala, and compare the recorded I654 / 1077 value with D -Pro and D -Ala aqueous solution was compared. There was almost no significant difference in the I654 / 1077 values of the spiked sample and the aqueous solution, indicating that the method has high reliability and low interference in actual sample analysis. D -Pro and D -Ala concentration. The spike concentrations were 0, 20, 100, and 200 μM, and the spike recovery was 98.6% to 109.4%, with a relative standard deviation (RSD) of less than 4.7%. The above results show that the biosensor has high accuracy and can detect early gastric cancer patients D -Pro / D Therefore, the SERS detection of Co-TA@Ag in saliva samples D -Pro and D -Ala's method has good practicality and has the potential to diagnose early gastric cancer noninvasively at the point of care.
[0114] Table 1 Saliva samples from volunteers without and with gastric cancer D -Pro (D-proline) and D-Ala (D-alanine) concentration measurement results
[0115]
[0116] The present invention synthesizes Co-TA@Ag NPs in an adjustable temperature environment through the step-by-step assembly of chiral nanozymes (Co-TA NPs) and in-situ interfacial reduction of different metals (Ag NPs). Polyphenol (TA), cobalt ions and formaldehyde (PA) are selected as polymerization ligands, metal sources and cross-linking agents, respectively. After the addition of PA, the metal ligands are bridged with cobalt ions to form cobalt polyphenol polymers. Subsequently, the unique redox properties of cobalt polyphenol are utilized to induce interfacial redox reactions on the surface of cobalt polyphenol, and cobalt polyphenol nanospheres loaded with AgNPs are successfully synthesized. At the same time, the signal molecule 3-MPBA is used to react with D -Ala and D -Pro undergoes a hydroxyl alcohol esterification reaction, thereby achieving the purpose of detection. This study uses the special selectivity and redox properties of the biosensor to develop a low-cost, rapid, and simple real-time monitoring method for gastric cancer in saliva samples. D -Pro and D -Ala abnormal levels. This provides a new perspective for clinical treatment and a new idea for biomarker detection and diagnosis of diseases. Importantly, the system is effective even for patients with early-stage cancer. We hope that this method can pave the way for clinical analysis of non-invasive screening for gastric cancer, provide appropriate and accurate diagnosis for more potential patients, and improve their prognosis.
[0117] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above invention concept. For example, the above features are replaced with the technical features with similar functions disclosed in this application (but not limited to) by each other to form a technical solution.
Claims
1. A rapid detection reagent for gastric cancer markers in saliva, characterized in that: The detection reagent comprises a composite nano material and a signal molecule 3-MPBA, wherein the composite nano material is a composite material shell structure of cobalt-polyphenol nanospheres encapsulating silver nanoparticles.
2. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 1, characterized in that: The following steps are involved: S11, dissolving F127 in a mixed solution of ethanol and ammonia and stirring the mixture, adding tannic acid solution and formaldehyde solution to react, and adding Co(NO3)2 solution to perform hydrothermal treatment, and obtaining a Co-TA nanocomposite material after centrifugal drying; S12, adding the silver ammonia solution to the Co-TA nanocomposite material to react, to obtain a Co-TA@Ag solution; S13, adding 3-MPBA solution and acetate buffer to the Co-TA@Ag solution, and incubating at room temperature to finally obtain a detection reagent.
3. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 2, characterized in that: In step S11, the mass of F127 is 0.1-0.3 g; the mixed solution of ethanol and ammonia is configured in the following proportions: the volume of ethanol is 8-10 ml, the volume of ultrapure water is 30-50 ml; the mass fraction of ammonia solution is 25 wt%, and the volume is 0.1-0.5 mL; the stirring time is 30-60 min.
4. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 2, characterized in that: In step S11, the volume of the tannic acid solution is 4-5 mL, the mass fraction of the formaldehyde solution is 37 wt %, the volume of the formaldehyde solution is 4-5 mL, and the reaction time of the tannic acid solution and the formaldehyde solution is 12-24 h.
5. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 2, characterized in that: In step S11, the concentration of the Co(NO3)2 solution is 80-100 mg / mL, the volume of the Co(NO3)2 solution is 1-2 mL, the heating temperature of the hydrothermal treatment is 80-100°C, and the heating time is 10-12 h; the centrifugal speed is 7000 rpm, and the centrifugal time is 10-15 min.
6. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 2, characterized in that: In step S12, the volume of the Co-TA nanocomposite material after dilution is 20-30 mL, the silver ammonia solution is added at a rate of 100-300 μL / min, the concentration of the silver ammonia solution is 10-30 mg / mL, and the volume of the silver ammonia solution is 10-20 mL; the reaction time of the silver ammonia solution and the Co-TA nanocomposite material is 20-50 min.
7. The method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 2, characterized in that: In step S13, the volume of the Co-TA@Ag solution is 50-100 μL, the volume of the 3-MPBA solution is 10-100 μL, the concentration of the 3-MPBA solution is 50-100 μM, the volume of the acetate buffer is 10-50 μL, the concentration of the acetate buffer is 5-10 mM, the pH of the acetate buffer is 3.6, and the room temperature incubation time is 3-6 h.
8. Use of a detection reagent prepared by the method for preparing a rapid detection reagent for gastric cancer markers in saliva according to any one of claims 2 to 6 in detecting gastric cancer markers contained in saliva, characterized in that: The following steps are involved: S21, diluting the saliva sample to be tested with PBS buffer, centrifuging and filtering with a filter membrane to obtain a sample to be tested; S22, reacting the sample to be tested with the detection reagent to determine the sample value, recording the intensity response of the Raman spectrometer, and calculating the difference determined according to the standard curve D -Pro / Ala concentration, each of the tested samples was repeated multiple times.
9. Use of the detection reagent prepared by the method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 8 in detecting gastric cancer markers contained in saliva, characterized in that: In step S21, the volume of the sample to be tested is 1-2 mL, the concentration of the PBS buffer is 10 mM, the pH is 7.4, and the volume is 5-10 mL; the centrifugal speed is 3000-5000 rpm, the centrifugal time is 5-10 min, and the pore size of the filter membrane is 0.45 μm.
10. Use of the detection reagent prepared by the method for preparing a rapid detection reagent for gastric cancer markers in saliva according to claim 8 in detecting gastric cancer markers contained in saliva, characterized in that: In step S22, the Raman spectrometer measurement conditions are: laser wavelength is 585-785 nm, laser power is 30-50 mW, and signal integration time is 1-5 s.